Decetralization & Its Discontents : An Essay on Class, Political Agency and National Perspective in Indonesian Politics - Lane, MAX (ISEAS, 2014)
Decentralization is a major trend in Indonesia since the first decades of that nation under Sukarno and Suharto. Max Lane is justly treasured for illuminating those first decades, for example, through his translations of Pramoedya Ananta Toer, and his excellent book, Unfinished Nation: Indonesia Before and After Suharto. Anyone who seeks insights into the current trend of decentralization, whether in Indonesia or other parts of the world, will find this work cogent